Implementation of mobile eye tracking systems for preventing emergency situations based on monitoring of driver behavior - Krivoulya, G.; Tkachov, V.; Tokarev, V.; Hunko, M. (My University, 2019)
Modern studies have shown that lack of sleep and, hence, a slowdown in the reaction speed and drowsiness can be as dangerous as a state of alcoholic intoxication i.e. a delayed reaction and a decrease in concentration [1]. As a solution to this problem, an approach is proposed for the development of active safety systems (ASS) aimed at preventing emergencies based on monitoring the behavior of a vehicle driver and timely notification of the driver about the current situation by generating context-oriented recommendations.
Keywords: eye tracking